Faktor-Faktor yang Berhubungan dengan Persepsi Remaja Tentang Lesbian, Gay, Biseksual, dan Transgender (LGBT) di SMP Negeri 24 Padang - Febrina Febrina; Waldatul Hamidah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Based on the HIV/AIDS information system report of the West Sumatra provincial office, it was stated that Padang City with the number of AIDS cases reported in 2021 recorded 280 people infected with HIV from January to November 2023. The Padang City Health Office stated that the dominant cause with the highest risk of residents infected with HIV AIDS was men who have sex with men (MSM), there was one case of MSM at SMP Negeri 24 Padang. The purpose of this study was to determine the factors related to adolescent perceptions of LGBT at SMP Negeri Padang in 2024.This type of research is